Intranasal Sendai virus‐based SARS‐CoV‐2 vaccine using a mouse model - Morimoto, Satoru; Saeki, Koichi; Takeshita, Masaru; Hirano, Kunio; Shirakawa, Mariko; Yamada, Yumiko; Nakamura, Shiho; Ozawa, Fumiko; Okano, Hideyuki (Genes to cells : devoted to molecular & cellular mechanisms, 2023)
The coronavirus disease 2019 (COVID‐19) epidemic remains worldwide. The usefulness of the intranasal vaccine and boost immunization against severe acute respiratory syndrome‐related coronavirus (SARS‐CoV‐2) has recently received much attention. We developed an intranasal SARS‐CoV‐2 vaccine by loading the receptor binding domain of the S protein (S‐RBD) of SARS‐CoV‐2 as an antigen into an F‐deficient Sendai virus vector. After the S‐RBD‐Fd antigen with trimer formation ability was intranasally administered to mice, S‐RBD‐specific IgM, IgG, IgA, and neutralizing antibody titers were increased in serum or bronchoalveolar lavage fluid for 12 weeks. Furthermore, in mice that received a booster dose at week 8, a marked increase in neutralizing antibodies in the serum and bronchoalveolar lavage fluid was observed at the final evaluation at week 12, which neutralized the pseudotyped lentivirus expressing the SARS‐CoV‐2 spike protein, indicating the usefulness of the Sendai virus‐based SARS‐CoV‐2 intranasal vaccine. We developed an intranasal SARS‐CoV‐2 vaccine by loading the receptor binding domain of the S protein (S‐RBD) of SARS‐CoV‐2 as an antigen into an F‐deficient Sendai virus vector. After the S‐RBD‐Fd antigen with trimer formation ability was intranasally administered to mice, S‐RBD‐specific IgM, IgG, IgA, and neutralizing antibody titers were increased in serum or bronchoalveolar lavage fluid for 12 weeks. Furthermore, in mice that received a booster dose at week 8, a marked increase in neutralizing antibodies in the serum and bronchoalveolar lavage fluid was observed at the final evaluation at week 12, which neutralized the pseudotyped lentivirus expressing the SARS‐CoV‐2 spike protein, indicating the usefulness of the Sendai virus‐based SARS‐CoV‐2 intranasal vaccine.